Ideal selves as identity management strategies - Dumont, K.; Waldzus, S. (International Journal of Intercultural Relations, 2015)
This research addresses the relationship between ideal selves and social context from a social identity perspective. Based on Social Identity Theory (Tajfel and Turner, 1979 and Tajfel and Turner, 1986) and related research, it is argued that ideal selves stand in a functional relationship with identity management strategies and that, consequently, shared beliefs about relevant intergroup relations influence the preferences for ideal selves. Three studies conducted with black and white adolescent and adult South Africans tested the assumption. The overall results of the studies confirmed that whether ideal selves corresponding to social change, social mobility or social creativity were preferred depended on whether the intergroup relations between black and white South Africans were perceived as secure or insecure.